Analysis of Human Resources Management in Improving Learning Strategies at MAN 2 Situbondo During the Covid-19 Pandemic - Turmudi, Imam (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2022)
This study aimed to determine learning strategies in the New Normal Era. In the last few years, Indonesia especially experienced the Covid 19 disaster, which caused all elements of life to experience a new era to live life. This field study was conducted at the Madrasah Aliyah Negeri 2 Situbondo institution because the institution in the teaching and learning process must use effective and efficient strategies to support ongoing learning and to find out Analysis of Human Resource Management in the New Normal Era’s improving learning strategies. The method employed in this study is a qualitative descriptive analysis study strategy. In the new normal era, human resource management enhances learning techniques through efforts, mature readiness, and debriefing in terms of Information Technology abilities and virtual learning habits, according to the survey results. The most effective learning method in the new normal period is to adhere to the regulations set forth by the Ministry of Education and Culture regarding virtual learning on a platform that has been approved. In order to reduce misunderstandings between teachers and students, it is essential that both students and teachers have the necessary tools, credentials, and awareness of the factors that will determine the course of learning. To prevent lying, being lazy, and cheating on tests, students study at home under the guidance and supervision of their parents. in order to maintain the standards of ethics, morals, and norms in academia.